Power, Violence, and the Paradox of Founding in John Ford’s The Man Who Shot Liberty Valance: An Arendtian Approach - Dees, Russell L. (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2015)
John Ford’s The Man Who Shot Liberty Valance is widely regarded as one of his best and darkest films and as a deep meditation on the American foundation myth. This article examines issues raised by John Ford’s film through distinctions Hannah Arendt developed between ‘power’ and ‘violence’ in her 1969 essay “On Violence” and through her analysis of foundation myths in her 1963 book On Revolution and places them in a broader context of political philosophy. Through this conceptual apparatus, we may gain new insight into the way John Ford’s film grapples with issues of law and politics. Moreover, the film provides concrete illustrations of some of the more abstract concepts in Hannah Arendt’s writings.